Examination of the effect of COVID‐19 on sexual dysfunction in women. Issue 3 (27th December 2020) - Kaya, Yeliz; Kaya, Coşkun; Tahta, Tuğba; Kartal, Tuğba; Tokgöz, Vehbi Yavuz
Abstract: Objective: To investigate the effect of COVID‐19 on sexual dysfunction in women. Material and Methods: The women diagnosed with COVID‐19 and hospitalised at a tertiary hospital were included. They completed the Introductory Data Form, the Female Sexual Function Index‐(FSFI) and the Short Form‐36 Quality of Life Scale (SF‐36). Results: Fifteen women between the ages of 19‐49 who completed the treatment protocol, discharged at least 14 days before and who had not been diagnosed as sexual dysfunction; sexually active earlier were included in the study. It was detected that weekly sexual intercourse before and after COVID‐19 significantly differed ( P = .047). The frequency of relationships decreased statistically after COVID‐19. The mean value of the FSFI satisfaction score differs from COVID‐19 before and after diagnosis ( P = .012). The mean satisfaction score before COVID‐19 was 3.47, and after COVID‐19 was 2.93. The score of the subgroups of FSFI did not differ from COVID‐19 before and after diagnosis ( P > .050). The median value of SF‐36 pain differs from COVID‐19 before and after diagnosis ( P = .008). Conclusion: It was concluded that the frequency of sexual intercourse and sexual satisfaction in women decreased after COVID‐19 disease, and the quality of life scores did not change in a statistically significant way.